The Effect Of Aflatoxin B1 And Ochratoxin A On Tumor Related Genes In Immortalized And Breast Cancer Cells - Ahmed Adam, Mowaffaq Adam (2019)
Mycotoxin contamination of food commodities caused by fungal strains such as Aspergillus and Penicillium is common in countries with tropical weather such as Malaysia due to the conditions that sustains their growth and development. Mycotoxins have been reported to cause severe food poisoning, liver damage and were proven carcinogenic to kidney and liver cells. The carcinogenic nature of Aflatoxin B1 and Ochratoxin A could increase the risks of breast cancer and an investigation on a molecular level need to be carried out to confirms it.